Design and Development of a Litho-code ID based electronic entry-control system - Umma Hany; Forhad Ebn Anwar; Nadiya Mahjabin; Sheesh Islam; Farzana Alam (Institute of Advanced Engineering and Science, 2012)
Different card operated entry control systems have been developed. However, it is desired that the system is reliable, easy to implement and available at market. In this paper, we design and develop an electronic entry control system which is based on an ID card and ID card reader. In our system, the ID card contains encoded Litho-code ID and the card reader is used to read the encoded ID. We develop offline Software to collect user information, save data and to print the ID card. We design and develop the electronic card reader to capture the ID using infra-red (IR) sensors and for computer interfacing. We develop online software to process the signals exchanged between the card reader and CPU. In this paper, first we present the system layout and design outline. Then we explain the development and implementation methodology. Finally, we test the system and present the results.DOI:http://dx.doi.org/10.11591/ijece.v2i4.705